2019
DOI: 10.29252/jcmh.6.1.20
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Compassion-based Therapy on Post Traumatic Growth in Mothers of Children with Attention Deficit/Hyperactivity Disorder

Abstract: Background and Purpose: Children with attention deficit / hyperactivity disorder (ADHD) suffer from developmental and functional defects that can cause serious damages to the family, including mother-child relationships. This study sought to determine the effectiveness of compassion-based therapy on post-traumatic growth in mothers of children with ADHD. Method: This study was a semi-experimental study with pretest-posttest control group design. The sample of this study included 20 mothers with children with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Another finding of the research showed that Compassion-Focused Therapy and Cognitive Behavioral-Therapy lead to an increase in post-traumatic growth in sexually abused girls. This finding is consistent with the results of prior studies (Ha et al, 2019;Kiarasi et al, 2022;Navab et al, 2019;Salemi et al, 2017;Zamani et al, 2021). In explaining this finding, it can be said that compassion therapy promotes kindness and compassion towards hardships, sufferings, and experiences, leading individuals to blame themselves less.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Another finding of the research showed that Compassion-Focused Therapy and Cognitive Behavioral-Therapy lead to an increase in post-traumatic growth in sexually abused girls. This finding is consistent with the results of prior studies (Ha et al, 2019;Kiarasi et al, 2022;Navab et al, 2019;Salemi et al, 2017;Zamani et al, 2021). In explaining this finding, it can be said that compassion therapy promotes kindness and compassion towards hardships, sufferings, and experiences, leading individuals to blame themselves less.…”
Section: Discussionsupporting
confidence: 94%
“…Mahmoudi, Jaberi, and Rahimi (2013) standardized this questionnaire for the Iranian population and reported that the Persian version of this questionnaire includes four components: sense of inner strength, change in goals and priorities, sense of intimacy and closeness with others, and effort to maintain relationships with others. They reported that the correlation coefficient of scores from the double measurement was 0.94 (Kiarasi et al, 2022;Navab et al, 2019). In the present study, the Cronbach's alpha coefficient for the entire questionnaire was determined at 0.85.…”
Section: Post-traumatic Growthmentioning
confidence: 42%
See 2 more Smart Citations
“…The findings of this study indicated that this program improved attention in these children. This is consistent with the results of different researches (20)(21)(22)(23), all of which indicate the effectiveness of cognitive rehabilitation program on the amount of attention.…”
Section: Discussionsupporting
confidence: 92%